Mini Riset: Pengimplementasian Kurikulum Merdeka Belajar Di Kelas X SMA Negeri 1 Lendah, Kulon Progo - avivahrahmadini; Deti Novianti; Farid Setiawan (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This research is in the form of mini research which aims to determine the implementation an independent curriculum at SMA Negeri 1 Lendah. This simple research uses descriptive qualitative research methods. The informant for this simple research was 1 deputy principal for curriculum. In this simple research, the data collection technique is literature review, obtained from books, scientific articles and documents related to the problem topic, observations and interviews. This simple research was carried out for 1 day on November 2 2023. Based on the results of simple research obtained from interviews at SMA Negeri 1 Lendah, it was said that using the independent curriculum made students, especially class a love of culture and building each other's skills. However, SMA Negeri 1 Lendah also has challenges that must be faced to face this independent curriculum, namely in the aspect of the role of teachers in increasing creativity in creating the projects that will be carried out. Keywords:,,